2007
DOI: 10.3892/or.18.1.113
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chemotherapy on Ki-67, Bcl-2 and Bak expression in primary tumors and lymph node metastases of breast cancer

Abstract: The aim of this study was the analysis of Ki-67, Bcl-2 and Bak expression in primary tumor and axillary lymph node metastases of breast cancer as well as an attempt to assess preoperative chemotherapy influence on the mentioned markers with regard to changes in the morphological appearance of the primary tumor and its metastases. Immunohistochemical examinations of Ki-67, Bcl-2 and Bak expression were conducted on sections collected from 135 patients treated surgically on invasive ductal breast cancer. Sixty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 24 publications
1
14
1
Order By: Relevance
“…ER, PgR, HER2 and Ki67 status were available allowing determination of the tumour subtype, 46% (165) of patients had Luminal A disease (ER or PgR-positive, HER2-negative and low Ki67 <14%), 22% (81) had Luminal B disease (ER-or PgR-and HER2-positive or ER, PgR and high Ki67 (>14%)), 20% (72) had triple negative disease (ER-, PgR-and HER2-negative) and 10% (38) had HER2 enriched (ER-and PgR-negative, HER2-positive).…”
Section: Discovery Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…ER, PgR, HER2 and Ki67 status were available allowing determination of the tumour subtype, 46% (165) of patients had Luminal A disease (ER or PgR-positive, HER2-negative and low Ki67 <14%), 22% (81) had Luminal B disease (ER-or PgR-and HER2-positive or ER, PgR and high Ki67 (>14%)), 20% (72) had triple negative disease (ER-, PgR-and HER2-negative) and 10% (38) had HER2 enriched (ER-and PgR-negative, HER2-positive).…”
Section: Discovery Cohortmentioning
confidence: 99%
“…are associated with prognosis and or response to therapy in breast cancer [37][38][39] . Figure 3C and also for the cells used in the wst-1 assays Figure 4A.…”
Section: Due To the Associations Of Ikkα Expression With Clinical Outmentioning
confidence: 99%
“…Previously, we showed that pre-operative chemotherapy affects breast cancer metastases to lymph nodes to a considerably lesser degree as compared to primary tumors. In the case of significant damage to the primary tumor, followed by an inability to determine ER expression, we demonstrated that tumor assessment may successfully be performed by means of metastases to local lymph nodes (15,16). Although pre-operative chemotherapy did not significantly affect ER expression in the primary tumor, we observed its impact on the expression of proteins correlated with proliferation and apoptosis; therefore, it influences neoplastic process biology.…”
Section: Comparison Of Markers P-value R ----------------------------mentioning
confidence: 58%
“…As previously described (15,16), the proteins studied were not visualized due to substantial damage to primary tumor cells in 19 of the patients that underwent chemotherapy. Therefore, further analyses, including statistical evaluation, were performed in the group of 45 female patients with invasive ductal breast cancer, in which immunohistochemical evaluation of the markers examined was feasible despite preoperative chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation